STRESSORS OF MOTHER - ADMINISTRATORS IN HIGHER EDUCATION INSTITUTIONS - Michael C. Mabalay (Izdevnieciba "Baltija Publishing", 2018)
This study assessed the stressors of mother-administrators of three public and ten private Higher Education Institutions in the province of Nueva Ecija. The samples were 100 mother-administrators who perform administrative functions like that of the President, Vice President, Dean, Director and Department Heads. The descriptive method of research was used. Data from Administrative Stress Index (ASI) survey questionnaire were tallied and analyzed using frequency, weighted mean, percentage, cross-tabulation and analysis of variance. As to personal profile, majority of the mother-administrators were at the age group of 41-50, their length of service ranged from 1-8 years and majority of them were doctorate degree holders. The stress level of mother-administrators was found "low" to "mild" using the Administrative Stress Index (ADI) which was categorized such as administrative responsibility (X= 2.60) "mild", role expectations (x=2.39) "low", intrapersonal conflicts (x=2.37) "low", interpersonal relations (x=2.35) "low" and administrative constraints (x=2.33) "low". Most of the mother-administrators from private HEIs were stressed in preparation and allocating budgets resources (2.84) "mild", being involved in the collective bargaining process (2.84) "mild", attempting to meet social expectations (housing, friends, etc.) (2.84) "mild" and administering the negotiated contract (grievance, interpretations) (2.67) "mild" while, mother-administrators from public HEIs were stressed in trying to complete reports and other paperwork (2.62) described as "mild". Analysis of variance showed that there was no significant difference in the stress level and age with F-value (0.145806) and F-critical value (3.109311), furthermore, length of service has F-value (1.302064) and F-critical value (2.467493) and finally, educational attainment has F-value (0.027632) and F-critical value (3.090187) and the null hypothesis is accepted. The level of coping preference scale and coping factor of mother-administrators of higher education institutions revealed that the Coping Preference Scale (CPS) utilized were (35.71%) described as "often" with ranked 1, followed by (35.57%) described as "occasionally" with ranked 2, followed by (12.57%) described as "frequently" with ranked 3, next is (12.29%) described as "rarely" with ranked 4 and lastly, only (3.86%) described as "never" with ranked 5. This means that the mother-administrators of higher education institutions which uniformly reflected a rating of "often".